New advances in the method validation, extraction methods and measurement uncertainty for the determination of water-soluble hexavalent chromium in hydraulic cement - Ramírez Quesada, María Melania (2021)
The quantification of Cr (VI) in the cement matrix is highly important, given the possibility of suffering illnesses including dermatitis, induced nasal carcinoma, and DNA damage produced by inhalation of and/or direct contact with this substance by construction workers. This study presents an analytical validation of the determination of water-soluble Cr (VI) using Ultraviolet–Visible Spectroscopy (UV–Vis) with 1.5-diphenylcarbazide. To do so, different performance characteristics were determined: working interval, analytical sensitivity, linearity, limits of detection (LOD) and quantification (LOQ), as well as measurement uncertainty, in order to provide better metrological information about the performance of this method. The study also focused on evaluating the impact of use of different types of standard sands (ASTM C-778 and CEN) for preparing mortar cement and extracting water soluble Cr (VI) present in the cement. For this purpose, two cements with different concentrations (2.01 ± 0.21 and 0.75 ± 0.09 mg-kg−1) of Cr (IV) were created to evaluate extraction using three types of treatments: oxidized with potassium peroxidisulfite, non-oxidized, and an alternative method using cement paste. It was observed that mortar cement using ASTM C-778 sand tends to underestimate Cr (IV) content when concentrations are below 0.8 mg kg−1, while at higher concentrations of ~2.0 mg kg−1 it does not generate different results compared to those obtained using mortar cement made with CEN-standard sand. An alternative method called “paste extraction” also showed statistically comparable results with respect to standard mortar for both concentration levels evaluated. Finally, samples of cement marketed in Costa Rica were analyzed using different types of water soluble Cr (IV) extraction methods. The results show concentrations between 0.70 ± 0.13 mg kg−1 and 1.30 ± 0.13 mg kg−1, demonstrating that they comply with the limits established by international standards and national regulations in Costa Rica.